CORRELATION AND PATH ANALYSIS IN YIELD AND QUALITY TRAITS IN F3 AND F4 GENERATION OF CARMEN X DEVETÜYÜ-176 - Fatma Aykut Tonk; Deniz İştipliler; Muzaffer Tosun; Emre İlker; Gizem Çivi (Journal of Animal and Plant Sciences, 2018)
Cotton (Gossypium hirsutum L.) is one of the most important plants worldwide because of its fiber that is used as raw material for the textile industry. Since the dyes used in dyeing process negatively affect the environment, many people prefer to use natural colored cotton products. The objective of this study was to establish the inter-relationship and direct and indirect effect of various quality traits on seed cotton yield in colored cotton genotypes. The F3 and F4 generations of the cross between Carmen (white) and Devetüyü-176 (brown fiber) were used for selection process in terms of seed cotton yield per plant and fiber color. The measured quality traits in the selected genotypes from F3 and F4 generations were micronaire, fiber strength, fiber length, uniformity ratio, short fiber index, fiber elongation. Phenotypic correlation and path coefficients were calculated separately for each generation. As results of the correlation analysis, seed cotton yield was not negatively associated with fiber quality properties. It may be concluded that the selection for seed cotton yield and fiber color should be applied in early generations and fiber quality properties of the selected promising colored cotton genotypes can be determined in further generations of Carmen x Devetüyü-176.
Keywords: colored cotton; yield; fiber traits; correlation; path analysis